A microstructure-oriented mathematical model of a direct internal reforming solid oxide fuel cell. (1st June 2020) - Brus, Grzegorz; Raczkowski, Piotr F.; Kishimoto, Masashi; Iwai, Hiroshi; Szmyd, Janusz S.
Graphical abstract: Highlights: A new direct methane steam reforming mathematical model was proposed. The numerical simulation results were juxtaposed with experimental data with good agreement. The parametric studies of the direct reforming of methane was conducted. Abstract: A standard fuel cell requires hydrogen for operation; however, to achieve near-term applications fuel cells need to use the existing infrastructure and already available fuels such as methane. In this respect, solid oxide fuel cells are promising candidates for distributed stationary power generation. However, feeding methane directly into the anode is liable to carbon deposition at low temperatures or to cause thermal stress due to the endothermic steam-methane reforming reaction at high temperatures. Because of these drawbacks, direct chemical conversion of methane on the Ni-based anode has not been realized in practical applications so far. Therefore, numerical modeling plays a vital role to optimize the anode and thereby assure the safe operating condition of the direct reforming process. This paper presents experimental and numerical studies on the direct internal reforming solid oxide fuel cell. A microstructure-orientated mathematical model of micro-scale transport phenomena, chemical and electrochemical reactions in an anode-supported solid oxide fuel cell is developed. The model divides a cell-assembly into six computational subdomains to bypass typical numerical artifacts and assure a realistic charge-transfer distribution in the electrodes. The proposed novel mathematical model positively passed verification with the comparison of the calculated current-voltage characteristics with the experimental ones.